Perekrutan dan Kegiatan Anak Sebagai Kurir dalam Jaringan Peredaran Narkoba - Anton Prasetyo* (Universitas Airlangga, 2019)
Polrestabes satresnarkoba data for the third quarter in surabaya until 2018 in total there are 20 suspects with the drug as a courier. As many as 15 people have as users, dealers and courier 2 3 .So based on the advanced analysis was needed on how the recruitment of children as a courier in the trafficking of drugs and analyzes on efforts to satresnarkoba polrestabes surabaya in reducing activity the recruitment of children as drug couriers .The statute used is research approach , the conceptual approach and empirical legal using interviews as a primary data and the cases handled satresnarkoba polrestabes surabaya as secondary data. The pattern of recruitment carried out to make children as drug couriers is through the use of weak economic conditions of children and the inability of children to work so that children have no other way to get money for drugs other than being couriers. The use of child loyalty to his group colleagues, the use of trap patterns and threats is another way of recruiting children in drug syndicates. The effort to handle the recruitment of children as drug couriers by the Satresnarkoba Polrestabes Surabaya is done in a pre-emptive manner, namely through integrated coordination with BNN Surabaya City by exchanging information about children caught in drugs and drug syndicates detected. The formation of anti- drug student cadres and drug counseling for parents of students is a pre- emptive method carried out by the Satresnarkoba Polrestabes Surabaya. While the repressive method is carried out by the application of criminal procedural law, especially for drug dealers and dealers to break drug networks. Firm and measurable actions and various drug raids operations are expected to break the chain of drug trafficking, especially those targeting children to be used as couriers.